AESTHETICS OF SPORTS AS A SENSE OF BEAUTY AND HARMONY - Shadimetova Gulchehra Mamurovna (EPRA International Journal of Research and Development (IJRD), 2023)
This article pays attention to the importance of sports in human life, highlights the connection of sports with beauty and harmony as an aesthetic value, and beauty in sports is associated with the movement of an athlete.